2008
DOI: 10.1021/nl080080l
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Nanoparticles with Lipid Membrane

Abstract: A nanoscale range of surface feature curvatures where lipid membranes lose integrity and form pores has been found experimentally. The pores were experimentally observed in the l-alpha-dimyristoyl phosphatidylcholine membrane around 1.2-22 nm polar nanoparticles deposited on mica surface. Lipid bilayer envelops or closely follows surface features with the curvatures outside of that region. This finding provides essential information for the understanding of nanoparticle-lipid membrane interaction, cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
352
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(378 citation statements)
references
References 30 publications
23
352
0
3
Order By: Relevance
“…[43][44][45][46][47] The occurrence of the interaction depends on whether the amount of energy released from the binding of the MSNs with the RBC membrane (E i ) is able to overcome the amount of free energy required to bend the membrane and adapt to the surface of MSNs (E b ). The former energy is associated with the external surface area (i.e., accessible silanols) of MSN, 30 while the latter is proportional to the curvature or inversely proportional to the square of the radius (r) of the particle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[43][44][45][46][47] The occurrence of the interaction depends on whether the amount of energy released from the binding of the MSNs with the RBC membrane (E i ) is able to overcome the amount of free energy required to bend the membrane and adapt to the surface of MSNs (E b ). The former energy is associated with the external surface area (i.e., accessible silanols) of MSN, 30 while the latter is proportional to the curvature or inversely proportional to the square of the radius (r) of the particle.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, since surface curvature decreases with particle size, the bending energy required to wrap the large particles (E b ) is lower than the one needed to wrap the smaller particles. 43 This combination makes membrane wrapping and engulfment of l-MSN thermodynamically favorable. On the contrary, in order for the RBC membranes to wrap around smaller s-MSNs, they would have to attain a larger curvature (steeper angles over smaller areas) than they need for wrapping around the larger particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 An atomic force microscopy study revealed that substrate-supported silica nanoparticles with diameters ranging from 1.2 to 22 nm pierced the L-a-dimyristoyl phosphatidylcholine bilayer, whereas particles outside of that size range supported the L-adimyristoyl phosphatidylcholine membrane without pore formation ( Figure 1a). The incomplete bilayer formation was attributed to the unfavorable bending energy of the membrane forming a highly curved structure.…”
Section: Formation Of Lipid-nanostructure Hybrids and Their Structurementioning
confidence: 99%
“…These norms have been repetitively validated in experimental studies, 18,19 and larger nanoparticles (i.e., >22 nm) in turn are known to be wrapped up by a lipid bilayer. 12,15 These boundaries can be cumbersome when designing application-oriented nanocontainers, as specific nanoparticle properties (i.e., optical, thermal and/or magnetic) ; which make them desirable in the first place ; are mostly governed by their size. Superparamagnetic iron oxide nanoparticles (SPIONs) are a general paradigm: their superparamagnetic features make them ideal thermoregulators 24 for various medically oriented tasks (i.e., hyperthermia 25,26 or drug release 17,18,27,28 ) and are presently valued as contrast agents in magnetic resonance imaging.…”
mentioning
confidence: 99%